Chronic tenosynovitis of the hand caused by Mycobacterium heraklionense. Issue 3 (September 2016) - Aburjania, Nana; Hammert, Warren C.; Bansal, Meenakshi; Boyce, Brendan F.; Munsiff, Sonal S.
Abstract: Non-tuberculous mycobacteria are increasingly recognized as a cause of infection in both immunocompromised and immunocompetent hosts. Mycobacterium heraklionense is a recently described member of the Mycobacterium terrae complex. Herein we report a case of M. heraklionense chronic flexor tenosynovitis in the hand, managed with surgery and antibiotics.